Dampak Pembangunan Proyek Strategis Nasional (Bandara Internasional Yogyakarta) terhadap Dinamika Penggunaan Lahan - Utami, Westi; Sugiyanto, Catur; Rahardjo, Noorhadi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
This paper aims to map land use change, pattern, and direction of built-up land development, before, during, and after the development of Yogyakarta International Airport. The data source employed was Pleiades imagery with a spatial resolution of 0.5 m. The visual method was used for image interpretation and the accuracy test was conducted through the confusion matrix. Land use change data obtained by overlay. The distribution pattern is determined by the average nearest neighbour, while the direction of development of built-up land is determined by the standard deviational ellipse The results indicate that the land use map has a very high accuracy of 92.52%. Moreover, the results of the overlay showed that land use changes occurred very massively, in that within eight years there were decreases of mixed plantations decreased by 528.17 Ha and of agricultural land by 112.66 Ha. On the other hand, there was a significant increase in residential area of 29.42 Ha and a service and trade area of 11.2 Ha. The results show the ratio value of the built-up land pattern in 2014 of 0.63, in 2018 of 0.59 and in 2022 of 0.33, with this value the built-up land pattern is clustered. The results showed that there was a change in the direction of the built land pattern which was initially eastward changed to the northeast parallel to the arterial road. Monitoring the pattern of land use dynamics is an important part in planning and regulating spatial patterns and the direction of regional development.